2007
DOI: 10.1080/00150190701518703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Optical Purity on the Phase Sequence of an Antiferroelectric Liquid Crystal, MHPOBC, under Pressure

Abstract: The influence of the optical purity on the phase sequence of an antiferroelectric liquid crystal, MHPOBC, under pressure was studied by dielectric and switching current measurements. In the case of R:S = 75:25, the phase sequence is independent of pressure up to 150 MPa. As the pressure is increased, the temperature width of the ferroelectric SmC * phase widens slightly but that of the antiferroelectric SmC * A phase narrows a little. On the other hand, the ferroelectric SmC * phase in the case of R:S = 100:0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…of SmC à phase and optical purity From the results, including those of previous studies, 15,16) the SmC à phase vanished under pressure above 80%ee and widened with pressure below 50%ee. To understand this difference, the relationship between the initial differential of the pressure for the temperature width of the SmC à phase, dðÁT SmC Þ=dp, and the optical purity is shown in Fig.…”
Section: Relationship Between Pressure Dependence Of Widthmentioning
confidence: 67%
See 1 more Smart Citation
“…of SmC à phase and optical purity From the results, including those of previous studies, 15,16) the SmC à phase vanished under pressure above 80%ee and widened with pressure below 50%ee. To understand this difference, the relationship between the initial differential of the pressure for the temperature width of the SmC à phase, dðÁT SmC Þ=dp, and the optical purity is shown in Fig.…”
Section: Relationship Between Pressure Dependence Of Widthmentioning
confidence: 67%
“…14) In previous papers, we reported that the SmC Ã phase in an AFLC, rectus 4-(1-methylheptyloxycalbonyl) phenyl 4 0 -octyloxybiphenyl-4carboxylate (R-MHPOBC, MHPOBC 100%ee), disappears under pressure, 15) but that it remains in MHPOBC (R : S ¼ 7:5 : 2:5, 50%ee). 16) Thus, there is no systematic change in these results. To clarify the reasons why any particular variety should be present, we measure the complex dielectric constants of two different optical purities of MHPOBC and report on the pressure-temperature (p-T ) phase diagrams and stability of the SmC Ã phase under pressure.…”
Section: Introductionmentioning
confidence: 77%